2013
DOI: 10.3133/sir20135045
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of groundwater system and simulation of regional groundwater flow for North Penn Area 7 Superfund site, Montgomery County, Pennsylvania

Abstract: conducted aquifer-interval isolation (packer) testing. Randall W. Conger conducted geophysical logging. J. Jeffrey Starn provided guidance on probabilistic modeling, and Richard B. Winston provided guidance on model preprocessing. The authors gratefully acknowledge the assistance of U.S. Environmental Protection Agency (USEPA) project managers Deanna Moultrie-Jackson and David Turner, the guidance of USEPA hydrogeologist Kathy Davies, and the cooperation of CDM Federal Programs Corporation (USEPA contractor) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Simulated groundwater-flow paths under 2005 conditions (Senior and Goode, 2013) from known sources of soil contamination were consistent with the distribution of contaminants in groundwater determined from the autumn 2005 sampling, including apparent separate plumes of CFC-11 and CFC-113. In 2010, the EPA collected another round of groundwater samples in the western part of North Penn Area 7 that showed large decreases in contaminant concentrations compared to 2005-06 results (CDM Federal Programs Corporation, 2011a, b;David Turner, EPA, written commun., 2014).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Simulated groundwater-flow paths under 2005 conditions (Senior and Goode, 2013) from known sources of soil contamination were consistent with the distribution of contaminants in groundwater determined from the autumn 2005 sampling, including apparent separate plumes of CFC-11 and CFC-113. In 2010, the EPA collected another round of groundwater samples in the western part of North Penn Area 7 that showed large decreases in contaminant concentrations compared to 2005-06 results (CDM Federal Programs Corporation, 2011a, b;David Turner, EPA, written commun., 2014).…”
Section: Introductionmentioning
confidence: 71%
“…From 2000 to 2005, USGS collected groundwater-level, geophysical, and aquifer-test data to describe the groundwater system and to provide a basis for the simulation of groundwater flow (Senior and Ruddy, 2004;others, 2005, 2008). Simulations of steady-state regional groundwater flow for periods of different pumping conditions (1990,1996,2000,2005) showed that directions of groundwater flow changed in response to changes in pumping (Senior and Goode, 2013). Senior and Goode (2013) also showed that the observed spatial distribution of contaminants was generally consistent with advective transport by groundwater flow from known source areas.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations